Study on Non-Prosecution Criteria for Dangerous Driving Crime of Driving a Motor Vehicle on a Road While Intoxicated - Hao Song (Law and Economy, 2022)
After the SPSS analysis of 577 non-prosecution cases in Shanghai, it is found that the standard of non-prosecution for drunk-driving dangerous driving cases is still not uniform. There are three main problems: blood alcohol concentration standard is vague and quite different; road type preference is inconsistent; vehicle, damage and criminal record do not have a significant impact on non-prosecution. In this paper, a standard model of “1 + X” with hemol concentration as the main body and assisted by other relevant factors is constructed, which is specifically hemol concentration (50%), minor circumstances (30%), confession attitude (15%) and other matters (5%). The above 75 points are preliminarily determined as pass points for non-prosecution. As a specific application of discretionary non-prosecution, the standard model of “1 + X” for non-prosecution reflects the organic combination of discretionary non-prosecution and leniency for confession system.